PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN OUTSOURCING PT CIPTA NINDITA NUSAPALA - Purwatiningsih, Purwatiningsih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine and analyze the effect of training and work motivation on the performance of outsourcing employees at PT Cipta Nindita Nusapala. The population of this study was taken from several samples of employees who work at PT Cipta Nindita Nusapala with a total of 50 people. This analysis uses a quantitative approach with a Multiple Linear Regression test analysis model obtained through a questionnaire that has been filled out by the respondents who have been determined. The test data used in this study is the classical assumption test consisting of the Multicollinearity test, Normality test, and heteroscedasticity test, hypothesis testing using simultaneous test (F test) and partial test (t test) and management performed using SPSS 26.0. The results of regression analysis show that the level of significance of training is not significant on employee performance. The results of regression analysis show that it is significant on employee performance and joint testing (simultaneous) shows that there is a significant effect between the independent variable and the dependent variable..